The Case for Tectonic Control on Erosional Exhumation on the Tropical Northern Andes Based on Thermochronology Data. Issue 4 (12th April 2021) - Pérez‐Consuegra, N.; Hoke, G. D.; Mora, A.; Fitzgerald, P.; Sobel, E. R.; Sandoval, J. R.; Glodny, J.; Valencia, V.; Parra, M.; Zapata, S.
Abstract: The tropical Northern Andes constitutes a great area to explore the interaction of tectonics and climate on the evolution of orogenic topography, as they are tectonically active, have steep gradients in relief and precipitation, and were less affected by Quaternary glaciations than high‐latitude mountains. This study combines new and published thermochronology along ∼500 km of the Eastern Cordillera in Colombia to explore what controls the rates of Miocene and Pliocene exhumation, including: (1) variations in late Cenozoic paleoclimate, (2) orographic precipitation or (3) variation in rock uplift associated with structural heterogeneities along the eastern flank of the range. New thermochronology data consists of 27 apatite and seven zircon (U‐Th)/He ages and five apatite fission track ages. Thermal history models show that rock cooling as a result of erosional exhumation has occurred everywhere in the Eastern Cordillera since at least the Miocene at spatially and temporally variable rates. Exhumation rates vary by an order of magnitude between various fault‐bounded blocks and there is no evidence for a spatially uniform increase in exhumation rates during the past ∼4–5 Ma that would indicate uniform climatic driven exhumation. The west (dry) to east (wet) gradient in precipitation rates across the Garzon Massif is not a major factor controlling the exhumation rates, as the exhumation rates are highest on the western drier flank. The greatest rates of exhumation of the Eastern Cordillera occur in the blocks associated with vigorous Cenozoic reactivation of inherited faults that had focused extension during Early Cretaceous rifting. Plain Language Summary: Understanding how tectonic and climatic forces influence erosion and shape mountains is important to understand the evolution of the landscapes through Earth's history. In this work we aim at determining how do tectonic processes and climate variability interact to shape Earth's surface? We studied the Eastern Cordillera of the Northern Andes, a mountain range located in Colombia in the tropics of South America. To obtain erosion (exhumation) rates, we used thermochronology, which is an innovative method that records—over timescales of millions of years—how fast the rocks located at great depths within the earth get cooled as they are transported to the surface while the overlying rock gets removed or eroded from the surface. The results show that the highest erosion rates occur near the places that have the most tectonically active faults. Higher rates of precipitation are not always associated with higher erosion rates. Thus, the precipitation rates along the Eastern Cordillera are not a major factor controlling the erosion rates. This study underscores the importance of a thorough characterization of the location of faults in a region and information about recent fault activity to the understanding of erosion and natural hazards in tropical mountains. Key Points: Rates and timing of exhumation are spatially variable along the Eastern Cordillera Precipitation plays a secondary role to tectonics in modulating exhumation Zones of highest exhumation are associated to inherited structures